Hydrogel capable of stably releasing hydrogen sulfide and preparation method thereof
By preparing hydrogels with high specific surface area and good pore structure, combined with sulfate reducing bacteria and polylactic acid microspheres, stable sustained and directed release of hydrogen sulfide is achieved, solving the problem of undirected release of hydrogen sulfide in the prior art, and improving the therapeutic effect and biosafety.
Patent Information
- Application Number
- CN202411789981.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to achieve directional delivery and controlled release of hydrogen sulfide in the body, resulting in poor treatment effect or toxicity risks.
By preparing a hydrogel that can stably release hydrogen sulfide, using materials such as polyvinyl alcohol (PVA) and glycidyl methacrylate (GMA), combined with sulfate reducing bacteria (SRB) and polylactic acid microspheres, a hydrogel with a high specific surface area and a good pore structure is formed to achieve sustained and directed release of hydrogen sulfide.
The growth rate of sulfate reducing bacteria (SRB) and the yield of hydrogen sulfide are improved, the stable and sustained release of hydrogen sulfide is achieved, the action time in the organism is extended, the targeted therapeutic effect on cancer cells is enhanced, and biosafety is ensured.
Smart Images

Figure CN119837823A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, and mainly to a hydrogel capable of stably releasing hydrogen sulfide and a preparation method thereof. Background Art
[0002] In recent years, gas therapy has attracted increasing attention for the treatment of major diseases such as cancer, inflammation, and cardiovascular disease. Hydrogen sulfide (H2S) is a gaseous signaling molecule that is considered to be the third type of gaseous signaling molecule after NO and CO. It plays a key role in various physiological and pathological states. Studies have shown that due to the differences in signaling pathways and metabolism between normal cells and cancer cells, high concentrations of exogenous H2S can specifically inhibit cancer cells through miRNA regulation, mitochondrial damage, uncontrolled intracellular acidification, or cell cycle arrest. It can also inhibit the activity of catalase (CAT) in cancer cells.
[0003] The effectiveness and biosafety of gas therapy depend on the concentration and location of the gas in the body. Excessive gas concentration in the blood may lead to potential toxicity, while insufficient gas concentration in diseased tissues may not achieve the best therapeutic effect. Ideally, the administered gas should accumulate selectively in the lesions rather than in the blood. Achieving directional delivery and controlled release of gas is a key challenge in gas therapy. Currently, the most commonly used H2S donor in biological research is sulfate, including quinine sulfate, which has antiviral, antiparasitic and antioxidant effects. However, these donors have some disadvantages as potential tumor therapeutics. Sulfate hydrolyzes immediately after dissolving in water and rapidly reacts with H2S and HS. - and S 2- The microspheres can be used to protect sulfate from being rapidly hydrolyzed, thus prolonging its action time in the organism.
[0004] In addition, the hypoxic tumor environment is very conducive to the growth of facultative anaerobes and intrinsic anaerobes. Sulfate-reducing bacteria (SRB) is an anaerobic microorganism distributed in the human intestine, stomach and mouth, with good hypoxia targeting ability. SRB uses sulfate as the main electron acceptor for respiration and can reduce SO4²⁻ to H2S under anaerobic conditions. Therefore, SRB can become a good H2S factory for treating tumors. In order to promote the growth of SRB in tumors and ensure a stable supply of SO4²⁻, it is necessary to protect the activity of SRB and supplement substrates containing sulfate. Hydrogel is a polymer with a structure and function similar to the natural extracellular matrix (ECM) and is widely used in the biomedical field, such as drug delivery systems, wound dressings, and tissue engineering repair. The three-dimensional network structure of hydrogel can provide a habitat for SRB, promote the growth of SRB, and improve SRB's tolerance to the external environment. Sulfate-containing microspheres loaded on hydrogels can be used as substrates to continuously provide SO4²⁻ for SRB. Summary of the invention
[0005] In view of the above problems in the prior art, the present invention provides a hydrogel that can stably release hydrogen sulfide and a preparation method thereof, with the aim of preparing a hydrogel that can increase the growth rate of SRB and the production of H2S, while having the effect of sustained release of H2S, and has the potential to be used in the targeted treatment of diseases such as cancer.
[0006] The technical solution of the present invention is as follows: A hydrogel capable of stably releasing hydrogen sulfide and a preparation method thereof, wherein the preparation method of the hydrogel comprises the following steps: (1) Preparation of polyvinyl alcohol hydrogel: polyvinyl alcohol (PVA) was added to a mixed solvent of distilled water and dimethyl sulfoxide (DMSO), nitrogen was introduced and heated at 135-145°C for 1.5-2.5 h. The mixed solution containing PVA was then cooled to 55-65°C and poured into a glass container precooled to 5-10°C. The mixture was placed at -15-25°C for 8-12 h to promote gelation. The formed frozen gel was soaked in distilled water for 90-102 h to completely remove the residual DMSO to obtain PVA hydrogel. (2) Preparation of modified PVA hydrogel: distilled water, the PVA hydrogel prepared in step (1), and glycidyl methacrylate (GMA) are added to a 250 ml three-necked round-bottom flask in sequence, the pH of the mixture is adjusted with nitric acid (HNO3), and the mixture is placed in a shaker at 250-350 rpm for 4-8 hours to obtain a uniformly dispersed suspension, and an acidic cerium ammonium nitrate (CAN) solution is dripped into the suspension as an initiator through a constant pressure reduction funnel at 35-45°C. After reacting for 4.5-5.5 hours, the product is immersed in distilled water for 22-26 hours to remove the homopolymer formed on the surface of the hydrogel, and then the hydrogel is vacuum dried at 35-45°C until the weight reaches a constant value; the dried hydrogel is immersed in a diethylamine aqueous solution at 24-28°C for reaction for 22-24 hours, and finally the product after the reaction is completed is vacuum dried at 35-45°C until the weight reaches a constant level to obtain a modified PVA hydrogel; (3) Preparation of polylactic acid microspheres: polylactic acid was dissolved in dichloromethane containing quinine sulfate to obtain a mixed solution, and the mixed solution was added dropwise to liquid paraffin containing 5 wt% Span 80, and stirred at 350-450 rpm for 20-30 min at 30, 35, and 40 °C, respectively. The dichloromethane was kept at 40 °C for 35-45 h to evaporate, and the obtained microspheres were collected by centrifugation and washed with n-hexane and 2-propanol to obtain polylactic acid microspheres, which were used as sulfate ion donors for SRB. (4) Preparation of hydrogel capable of stably releasing H2S: Sulfate-reducing bacteria (SRB) were cultured in fresh modified Postgate medium to obtain a fresh bacterial suspension, which was further diluted to 5×10 4 CFU / ml, the modified PVA hydrogel prepared in step (2) is cryogenically crushed with liquid nitrogen to obtain its flowable form, and is sterilized under high pressure to eliminate microbial contamination, the sterilized modified PVA hydrogel is added to the SRB suspension, stirred to fully mix the bacteria and the hydrogel material, and a uniform SRB / modified PVA hydrogel mixture is prepared, and finally the SRB / modified PVA hydrogel mixture is evenly mixed with the polylactic acid microspheres prepared in step (3) to obtain a hydrogel that can stably release H2S.
[0007] Preferably, in step (1), the mass ratio of polyvinyl alcohol to dimethyl sulfoxide is 1:(5-5.6), and the mass ratio of distilled water to dimethyl sulfoxide is 1:(3.7-4.2).
[0008] Preferably, in step (2), the ratio of GMA mass (g), distilled water volume (ml) and PVA hydrogel mass (g) is 1: (98-102): (4.5-4.7); the ratio of GMA mass (g) and CAN (ml) volume is 1: (34-38), and the pH of the mixture is adjusted to 5-6 with nitric acid.
[0009] Preferably, the volume ratio of diethylamine to distilled water in step (2) is 1:(0.8-1.2).
[0010] Preferably, in step (3), the ratio of the mass (g) of quinine sulfate, the volume (ml) of dichloromethane and the mass (mg) of polylactic acid is 1:(4.5-5.5):(335-425).
[0011] Preferably, in step (4), the ratio of the volume (ml) of the SRB suspension to the mass (mg) of the modified PVA hydrogel is 1:(9-11), and the ratio of the volume (ml) of the SRB / modified PVA hydrogel mixture to the mass (g) of the polylactic acid microspheres is 1:(2.5-4.5).
[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The hydrogel prepared by the present invention that can stably release hydrogen sulfide has a high BET specific surface area of about 30.88 m 2 / g, with higher porosity and finer pore structure, while promoting the transport of nutrients in the hydrogel, it provides more attachment points for sulfate-reducing bacteria (SRB), promotes the adhesion and proliferation of SRB, and improves the activity of SRB, so that the hydrogel prepared by the present invention has the ability to stably release hydrogen sulfide, and the release amount of hydrogen sulfide can reach 99μmol / L on the 9th day.
[0013] 2. The present invention introduces a positively charged diethyl functional group in the preparation process of the hydrogel, which can effectively adsorb polylactic acid microspheres containing quinine sulfate, and at the same time, under the synergistic effect of the hydrogel swelling behavior, the release time of sulfate ions is extended to 7 days. In addition, the hydrogel prepared by the present invention has good thermal stability and cell compatibility. The results of the cytotoxicity experiment show that the cell survival rate exceeds 85% within 72 hours, and it has application potential in the targeted treatment of diseases such as cancer. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Preparation of hydrogel in Example 1 Figure 2 FTIR spectrum of the hydrogel in Example 1 Figure 3 XPS spectra of the hydrogels of Example 1 and Comparative Example 1 Figure 4 TGA curves of hydrogels in Example 1 and Comparative Example 1 Figure 5 Nitrogen adsorption / desorption isotherms of (a) Comparative Example 1 and (b) Example 1 hydrogels Figure 6 The release of sulfate ions from the hydrogels of Example 1 and Comparative Example 1 Figure 7 The SRB growth curves of Example 1, Comparative Example 1 and the control group are shown in Table 1. Bacteria were cultured in a modified Postgate liquid medium and OD was measured at set time points. 340 Value (n=3) Figure 8 The concentration of hydrogen sulfide produced by Example 1, Comparative Example 1 and Control Group (n=3) Fig. 9 The cytotoxicity of the hydrogel in Example 1 and the hydrogel in Comparative Example 1 DETAILED DESCRIPTION The present invention is specifically described below by way of examples, which are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. It should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
[0015] Example 1 The preparation steps of the hydrogel capable of stably releasing hydrogen sulfide are as follows: (1) Preparation of polyvinyl alcohol hydrogel: 20 g of distilled water and 80 g of dimethyl sulfoxide (DMSO) were mixed evenly to obtain a mixed solvent. 15 g of polyvinyl alcohol (PVA) was added to the mixed solvent, nitrogen was introduced and heated at 140 °C for 2 h. The mixed solution containing PVA was then cooled to 60 °C and poured into a glass container precooled to 8 °C. It was placed at -20 °C for 10 h to promote gelation. Finally, the formed frozen gel was soaked in distilled water for 96 h to completely remove the residual DMSO to obtain PVA hydrogel.
[0016] (2) Preparation of modified PVA hydrogel: 110 ml of distilled water, 5.00 g of the PVA hydrogel prepared in step (1), and 1.1 g of glycidyl methacrylate (GMA) were added to a 250 ml three-necked round-bottom flask in sequence. The pH of the mixture was adjusted to 5.5 with nitric acid (HNO3) and placed in a shaker at 300 rpm for 6 h to obtain a uniformly dispersed suspension. 40 ml of acidic ammonium cerium nitrate (CAN) solution was added as an initiator at 40 °C through a constant pressure reduction funnel. The suspension was added, and after reacting for 5 hours, the product was immersed in distilled water for 24 hours to remove the homopolymer formed on the surface of the hydrogel, and then the hydrogel was vacuum dried at 40°C until the weight reached a constant value; 50 ml of diethylamine and 50 ml of distilled water were evenly mixed to obtain a diethylamine aqueous solution, and the dried hydrogel was immersed in the diethylamine aqueous solution at 26°C to react for 24 hours, and the product after the reaction was completed was vacuum dried at 40°C until the weight reached a constant level to obtain a modified PVA hydrogel.
[0017] (3) Preparation of polylactic acid microspheres: 378 mg of polylactic acid was dissolved in 5 ml of dichloromethane containing 1 g of quinine sulfate to obtain a mixed solution. The mixed solution was added dropwise to 250 g of liquid paraffin containing 5 wt% of Span 80. The mixture was stirred at 30, 35, and 40 °C at 400 rpm for 25 min each. The mixture was kept at 40 °C for 40 h to evaporate the dichloromethane. The microspheres were collected by centrifugation and washed with n-hexane and 2-propanol to obtain polylactic acid microspheres, which were used as sulfate ion donors for SRB.
[0018] (4) Preparation of hydrogel capable of stably releasing H2S: Sulfate-reducing bacteria (SRB) were cultured in fresh modified Postgate medium to obtain a fresh bacterial suspension, which was then further diluted (5 × 10 4 CFU / ml), the modified PVA hydrogel prepared in step (2) is cryogenically crushed with liquid nitrogen to obtain its flow form, and is sterilized under high pressure to eliminate microbial contamination, 200 mg of the sterilized modified PVA hydrogel is taken, added to 20 ml of SRB suspension, and stirred to fully mix the bacteria and the hydrogel material to obtain an SRB / modified PVA hydrogel mixture, and the SRB / modified PVA hydrogel mixture is evenly mixed with the polylactic acid microspheres prepared in step (3), wherein the ratio of the SRB / modified PVA hydrogel mixture volume (ml) to the microsphere mass (g) is 1:3.5, and finally a hydrogel that can stably release H2S is obtained.
[0019] Example 2 (1) Preparation of polyvinyl alcohol hydrogel: 20 g of distilled water and 75 g of dimethyl sulfoxide (DMSO) were mixed to obtain a mixed solvent. 15 g of polyvinyl alcohol (PVA) was added to the mixed solvent, nitrogen was introduced and heated at 135 °C for 1.5 h. The mixed solution containing PVA was then cooled to 55 °C and poured into a glass container precooled to 5 °C. It was placed at -15 °C for 8 h to promote gelation. Finally, the formed frozen gel was soaked in distilled water for 90 h to completely remove the residual DMSO to obtain PVA hydrogel.
[0020] (2) Preparation of modified PVA hydrogel: 108 ml of distilled water, 4.95 g of the PVA hydrogel prepared in step (1), and 1.1 g of glycidyl methacrylate (GMA) were added to a 250 ml three-necked round-bottom flask in sequence. The pH of the mixture was adjusted to 5 with nitric acid (HNO3) and placed in a shaker at 250 rpm for 4 h to obtain a uniformly dispersed suspension. 37.5 ml of acidic ammonium cerium nitrate (CAN) solution as an initiator was added dropwise at 35 °C through a constant pressure reduction funnel. The suspension was added, and after reacting for 4.5 hours, the product was immersed in distilled water for 22 hours to remove the homopolymer formed on the surface of the hydrogel, and then the hydrogel was vacuum dried at 35°C until the weight reached a constant value; 50 ml of diethylamine and 40 ml of distilled water were evenly mixed to obtain a diethylamine aqueous solution, and the dried hydrogel was immersed in the diethylamine aqueous solution at 24°C to react for 22 hours. The product after the reaction was vacuum dried at 35°C until the weight reached a constant level to obtain a modified PVA hydrogel.
[0021] (3) Preparation of polylactic acid microspheres: 335 mg of polylactic acid was dissolved in 4.5 ml of dichloromethane containing 1 g of quinine sulfate to obtain a mixed solution. The mixed solution was added dropwise to 225 g of liquid paraffin containing 5 wt% of Span 80. The mixture was stirred at 350 rpm for 20 min at 30, 35, and 40 °C, respectively. The dichloromethane was evaporated at 40 °C for 35 h. The microspheres were collected by centrifugation and washed with n-hexane and 2-propanol to obtain polylactic acid microspheres, which were used as sulfate donors for SRB.
[0022] (4) Preparation of hydrogel capable of stably releasing H2S: Sulfate-reducing bacteria (SRB) were cultured in fresh modified Postgate medium to obtain a fresh bacterial suspension, which was then further diluted (5 × 10 4 CFU / ml), the modified PVA hydrogel prepared in step (2) is cryogenically crushed with liquid nitrogen to obtain its flowable form, and is sterilized under high pressure to eliminate microbial contamination, 180 mg of the sterilized modified PVA hydrogel is taken, added to 20 ml of SRB suspension, and stirred to fully mix the bacteria and the hydrogel material to obtain an SRB / modified PVA hydrogel mixture, and the SRB / modified PVA hydrogel mixture is evenly mixed with the polylactic acid microspheres prepared in step (3), wherein the ratio of the SRB / modified PVA hydrogel mixture volume (ml) to the microsphere mass (g) is 1:2.5, and finally a hydrogel that can stably release H2S is obtained.
[0023] Example 3 (1) Preparation of polyvinyl alcohol hydrogel: 20 g of distilled water and 84 g of dimethyl sulfoxide (DMSO) were mixed to obtain a mixed solvent. 15 g of polyvinyl alcohol (PVA) was added to the mixed solvent, nitrogen was introduced and heated at 145 °C for 2.5 h. The mixed solution containing PVA was then cooled to 65 °C and poured into a glass container precooled to 10 °C. It was placed at -25 °C for 12 h to promote gelation. Finally, the formed frozen gel was soaked in distilled water for 102 h to completely remove the residual DMSO to obtain PVA hydrogel.
[0024] (2) Preparation of modified PVA hydrogel: 112 ml of distilled water, 5.17 g of the PVA hydrogel prepared in step (1), and 1.1 g of glycidyl methacrylate (GMA) were added to a 250 ml three-necked round-bottom flask in sequence. The pH of the mixture was adjusted to 6 with nitric acid (HNO3) and placed in a shaker at 350 rpm for 8 h to obtain a uniformly dispersed suspension. 41.5 ml of acidic cerium ammonium nitrate (CAN) solution was added dropwise as an initiator at 45 °C through a constant pressure reduction funnel. In the suspension, after reacting for 5.5 hours, the product is immersed in distilled water for 26 hours to remove the homopolymer formed on the surface of the hydrogel, and then the hydrogel is vacuum dried at 45°C until the weight reaches a constant value; 50 ml of diethylamine and 60 ml of distilled water are evenly mixed to obtain a diethylamine aqueous solution, and the dried hydrogel is immersed in the diethylamine aqueous solution at 28°C to react for 26 hours. The product after the reaction is completed is vacuum dried at 45°C until the weight reaches a constant level to obtain a modified PVA hydrogel.
[0025] (3) Preparation of polylactic acid microspheres: 425 mg of polylactic acid was dissolved in 5.5 ml of dichloromethane containing 1 g of quinine sulfate to obtain a mixed solution. The mixed solution was added dropwise to 275 g of liquid paraffin containing 5 wt% of Span 80. The mixture was stirred at 450 rpm for 30 min at 30, 35, and 40 °C, respectively. The dichloromethane was evaporated at 40 °C for 45 h. The microspheres were collected by centrifugation and washed with n-hexane and 2-propanol to obtain polylactic acid microspheres, which were used as sulfate ion donors for SRB.
[0026] (4) Preparation of hydrogel capable of stably releasing H2S: Sulfate-reducing bacteria (SRB) were cultured in fresh modified Postgate medium to obtain a fresh bacterial suspension, which was then further diluted (5 × 10 4CFU / ml), the modified PVA hydrogel prepared in step (2) is cryogenically crushed with liquid nitrogen to obtain its flowable form, and is sterilized under high pressure to eliminate microbial contamination, 180 mg of the sterilized modified PVA hydrogel is taken, added to 20 ml of SRB suspension, and stirred to fully mix the bacteria and the hydrogel material to obtain an SRB / modified PVA hydrogel mixture, and the SRB / modified PVA hydrogel mixture is evenly mixed with the polylactic acid microspheres prepared in step (3), wherein the ratio of the SRB / modified PVA hydrogel mixture volume (ml) to the microsphere mass (g) is 1:4.5, and finally a hydrogel that can stably release H2S is obtained.
[0027] Comparative Example 1 A preparation step of PVA hydrogel (1) Preparation of polyvinyl alcohol hydrogel: same as in Example 1.
[0028] (2) Preparation of polylactic acid microspheres: same as in Example 1.
[0029] (3) Preparation of SRB@PVA hydrogel: Sulfate-reducing bacteria (SRB) were cultured in fresh modified Postgate medium to obtain fresh bacterial suspension, which was further diluted (5×10 4 CFU / ml), the PVA hydrogel prepared in step (1) is cryogenically crushed with liquid nitrogen to obtain its flowable form, and is sterilized under high pressure to eliminate microbial contamination, 200 mg of the sterilized PVA hydrogel is taken, added to 20 ml of the SRB suspension, and stirred to fully mix the bacteria and the hydrogel material to obtain an SRB / PVA hydrogel mixture, and the SRB / PVA hydrogel mixture is evenly mixed with the polylactic acid microspheres prepared in step (2), wherein the ratio of the SRB / modified PVA hydrogel mixture volume (ml) to the microsphere mass (g) is 1:3.5, and finally SRB@PVA hydrogel is obtained.
[0030] Experimental methods The embodiments and comparative examples were tested, and the test methods of Fourier transform infrared (FTIR) spectroscopy, specific surface area, thermal stability test, sulfate ion release rate, H2S production, SRB in vitro growth and metabolism, sample cytotoxicity, etc. are as follows: Fourier transform infrared (FTIR) spectroscopy: The hydrogel prepared in step (2) of Example 1 was detected using a Thermo Scientific Nicolet iS20 FTIR Spectrometer (America).
[0031] X-ray photoelectron spectroscopy (XPS) test: The hydrogels prepared in step (2) of Example 1 and step (1) of Comparative Example 1 were tested using a Thermo Scientific K-Alpha spectrometer equipped with an AlKax ray source of 1486.6 eV.
[0032] Specific surface area: The N2 adsorption / desorption isotherms of the hydrogels prepared in step (2) of Example 1 and step (1) of Comparative Example 1 were measured, and the specific surface area was calculated using the Brunauer-Ett method. The samples were freeze-dried for 48 h to remove moisture and then degassed at 120 °C for 6 h.
[0033] Thermal stability test: Thermogravimetric analysis (TGA) of the hydrogels prepared in step (2) of Example 1 and step (1) of Comparative Example 1 was performed using a NETZSCH TG 209 thermal analyzer in an inert nitrogen atmosphere at a heating rate of 10°C / min over a temperature range of 25-600°C.
[0034] Sulfate ion sustained release rate: The polylactic acid microsphere / hydrogel composites (without SRB) prepared in Example 1 and Comparative Example 1 were immersed in phosphate buffer solution (PBS), sampled at predetermined time points, appropriately diluted, and analyzed by UV spectrophotometry (HP8543 UV-Vis scanning spectrophotometer; Agilent Technologies) at 276 nm to determine sulfate ion release.
[0035] H2S production: The concentration of H2S in the hydrogels prepared in Example 1 and Comparative Example 1 was determined by the methylene blue method. 100 μL of the sample was mixed with 0.85% (w / v) NaOH / Zn(Ac)2 solution, FeCl3 (13.3 mmol / L) and DMPD-HCl solution (10 mmol / L DMPD dissolved in 6 mol / L hydrochloric acid) in sequence, and the mixture was allowed to react in the dark for 20 minutes to form methylene blue (MB), and then the absorbance was measured at a wavelength of 670 nm using a UV-visible spectrophotometer (Agilent Cary60, USA). The concentration of H2S in the sample was determined using the standard curve of Na2S.
[0036] Growth and metabolism of SRB in vitro: Modified Postgate medium was prepared by dissolving 5.2 g of Postgate medium powder and 1.1 g of sodium D-lactate in 1000 mL of distilled water and then autoclaved at 121 °C for 15 min. 500 μL of SRB suspension (5 × 10 4 CFUml -1), the hydrogel samples were injected into separate 50 mL headspace bottles, and then each bottle was filled with 25 mL of modified Postgate medium and a certain amount of polylactic acid microsphere powder of quinine sulfate. The bottles were purged with N2 gas and placed in an anaerobic environment at 37 °C for bacterial culture. OD 340 The measurements were repeated three times every two days, and in addition, the H2S content was quantified daily using the methylene blue method.
[0037] Cytotoxicity of samples: The cytotoxicity of cell membranes was detected by in vitro cytotoxicity-indirect cytotoxicity assay. L929 mouse fibroblasts (ATCC NCTC clone 929: CCL1) were cultured in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum. The culture conditions were 5% carbon dioxide, 37°C, and relative humidity above 90%. Polyurethane (PU) was used as the blank control group. The membranes were immersed in the culture medium for 72 h. Then, the membranes and L929 cells were plated in 96-well plates at 1×10 5 The cells were allowed to interact overnight at a density of 10 cells / ml. After 24 h, 48 h and 72 h, the culture medium was changed to 10% 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) and incubated at 37°C for 4 h. The culture medium was removed and 100 μL of propylene glycol solution (0.04 MHCl) was added for incubation. The cell viability was determined by the MTT reduction method and the absorbance was measured at 570 nm using a microplate reader.
[0038] The test results are shown in the attached manual. Figures 1 to 9 .
[0039] The synthesis steps of the hydrogel prepared in Example 1 are as follows Figure 1 First, epoxy groups are introduced into the PVA hydrogel structure by free radical polymerization, and then diethylamine groups are added to form a hydrogel that can stably release hydrogen sulfide. The functional groups of the hydrogel that can stably release hydrogen sulfide in Example 1 are as follows: Figure 2 As shown in the FTIR spectrum of the hydrogel of Example 1, at 3292 cm -1 The absorption band at 1085 cm corresponds to the stretching vibration of OH. -1 The band at 1728 cm -1 The peak at 1321 cm-1 and 1236 cm-2 is related to the C=O stretching vibration caused by the methacryloyl group. -1 Two characteristic absorption bands of tertiary amine groups appeared at , which are the characteristic absorption bands of the CN bonds of aromatic amines, indicating that the diethylamine groups have been successfully introduced into the hydrogel.
[0040] The chemical composition and elemental composition of the hydrogel surface were analyzed using X-ray photoelectron spectroscopy (XPS). Figure 3The wide scan XPS spectra of the hydrogels of Example 1 and Comparative Example 1 show that the characteristic peaks of C1s (284.5 eV) and O1s (530.3 eV) exist in the hydrogel sample of Comparative Example 1. In contrast, the hydrogel of Example 1 shows characteristic peaks of C1s (285.1 eV), O1s (530.6 eV) and N1s (400.9 eV). The appearance of the N1s peak confirms the successful introduction of the diethylamine group. Table 1 lists the C, N and O contents of the two hydrogels. With the incorporation of glycidyl methacrylate and diethylamine in the hydrogel of Example 1, the ratio of C and N elements increases, while the ratio of O element decreases.
[0041] Table 1 XPS test values of Example 1 and Comparative Example 1 The thermal stability of the hydrogels prepared in Example 1 and Comparative Example 1 in a nitrogen atmosphere at 35-600°C was evaluated using thermogravimetric analysis (TGA). Figure 4 ), in the temperature range of 30~100℃, the weight loss of the hydrogels in Example 1 and Comparative Example 1 is attributed to the evaporation of water and solvent. In the hydrogel in Comparative Example 1 at 235℃ and the hydrogel in Example 1 at 208℃, a weight loss of 5% occurs, indicating the beginning of thermal degradation. Both hydrogels begin to decompose significantly when the temperature exceeds 260℃. The maximum degradation rates of the hydrogels in Comparative Example 1 and Example 1 occur at about 369℃ and 361℃, respectively. The thermal degradation curves show that the hydrogel in Example 1 exhibits thermal degradation characteristics very similar to those of the hydrogel in Comparative Example 1, while the hydrogel in Example 1 begins to decompose only at temperatures above 260℃, indicating that the hydrogel synthesized in the present invention has good thermal stability.
[0042] The adsorption properties of the hydrogels of Comparative Example 1 and Example 1 were studied using the BET method. Figure 5 The N2 adsorption / desorption isotherms of the two hydrogels show typical characteristics of type II mesoporous materials. The BET specific surface area of the hydrogel in comparative example 1 is about 22.33 m 2 / g, while the hydrogel in Example 1 has a higher BET specific surface area of about 30.88 m 2 / g. In porous materials, an increase in specific surface area is generally associated with higher porosity and finer pore structure, which affects the adsorption capacity of the material. Compared with Comparative Example 1, the hydrogel in Example 1 has a higher specific surface area, so it provides more adsorption sites for SRB (sulfate-reducing bacteria), enabling it to more effectively immobilize SRB. In addition, the high specific surface area of the hydrogel in Example 1 promotes the transport of nutrients within the hydrogel and promotes the utilization of sulfate ions by SRB.
[0043] In the controlled release experiment, the sulfate ion release performance of the hydrogels of Example 1 and Comparative Example 1 was compared. Figure 6 As shown. The results show that the hydrogel of comparative example 1 has a certain degree of sustained release ability of sulfate ions, and the sustained release time lasts until the 4th day. This is due to the three-dimensional network structure inside the hydrogel, which protects sulfate ions through polylactic acid microspheres containing quinine sulfate, thereby slowing down their release rate. In addition, the swelling behavior of the hydrogel further helps to delay the release of sulfate ions. However, compared with the hydrogel of comparative example 1, the hydrogel of example 1 shows a more superior sustained release ability, and the release time can be extended to the 7th day. This performance improvement is mainly due to the presence of positively charged diethyl functional groups on the side chains of the hydrogel of example 1, which effectively adsorbs the sulfur-containing polylactic acid microspheres and slows down the release of sulfate ions. The experimental results reveal that the hydrogel prepared by the present invention has a good sustained release ability of sulfate ions, and provides an effective method for maintaining a stable ion concentration of sulfate in a biological system.
[0044] To measure the growth of sulfate-reducing bacteria (SRB) in hydrogels, we used OD 340 The growth of SRB in Example 1 and Comparative Example 1 was evaluated by measuring the values. Figure 7 As shown, compared with the control group, SRB showed a superior growth trend in the hydrogels of Example 1 and Comparative Example 1, wherein in the hydrogel of Comparative Example 1, SRB reached a growth peak on the 9th day, while in the hydrogel of Example 1, SRB reached a growth peak on the 11th day, and the SRB count was higher. Therefore, the growth of SRB in the hydrogel of Example 1 was more favorable. This growth can be attributed to the fact that the specific surface area of Example 1 is higher than that of Comparative Example 1, which provides more attachment points for bacteria and promotes bacterial adhesion and proliferation. In addition, the high specific surface area of Example 1 enhances the continuous transport of nutrients in the hydrogel, further promoting the activity of SRB in the hydrogel of Example 1 for a longer period of time.
[0045] In order to evaluate the effect of hydrogel on the production of hydrogen sulfide (H2S) by sulfate-reducing bacteria (SRB), we used the methylene blue method to measure the level of hydrogen sulfide produced by SRB in the control group (without hydrogel), comparative example 1 and example 1. The experimental results are shown in Figure 8As shown, compared with direct growth in Postgate medium, SRB produced more hydrogen sulfide in Example 1 and Comparative Example 1, among which the yield in Example 1 was the highest, and the control group reached a maximum hydrogen sulfide yield of 77 μmol / L on the 7th day. In contrast, Comparative Example 1 and Example 1 had the largest hydrogen sulfide yields on the 8th and 9th days, reaching 82 μmol / L and 99 μmol / L, respectively. The increase in hydrogen sulfide production in Example 1 can be attributed to its physical and chemical properties. First, the three-dimensional porous structure of the hydrogel in Example 1 provides a larger specific surface area, which promotes the attachment and growth of bacteria, thereby increasing the production of hydrogen sulfide. Secondly, compared with the hydrogel in Comparative Example 1, the hydrogel in Example 1 has more favorable pore size and surface properties, providing more adhesion sites and a better growth environment for SRB, which leads to an increase in hydrogen sulfide production. Therefore, the hydrogel prepared in Example 1 significantly improves the growth activity and sulfate ion utilization efficiency of SRB.
[0046] With polyurethane (PU) as the control group, the MTT method was used to detect the cytotoxicity of the hydrogels of Example 1 and Comparative Example 1. The results are as follows: Fig. 9 As shown, the cell survival rate of the blank control group was close to 100%. Within 24, 48 and 72 hours, the cell survival rates of Comparative Example 1 were 95.19%, 91.73% and 88.39%, respectively, and the cell survival rates of Example 1 during the same period were 93.87%, 88.22% and 85.96%, respectively. These results show that exposure to the hydrogel prepared in Example 1 and Comparative Example 1 had no significant effect on the survival rate of L929 cells within 72 hours, and all cell survival rates exceeded 75%, meeting the toxicity level 1 of the standard toxicity grading system, indicating that the hydrogels of Comparative Example 1 and Example 1 are non-toxic. Therefore, the hydrogel prepared by the present invention that can stably release hydrogen sulfide has good cell compatibility and has potential application potential in the targeted treatment of diseases such as cancer.
[0047] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.
Claims
1. A hydrogel capable of stably releasing hydrogen sulfide and a preparation method thereof, characterized in that The preparation method of the hydrogel comprises the following steps: (1) Preparation of polyvinyl alcohol hydrogel: polyvinyl alcohol (PVA) was added to a mixed solvent of distilled water and dimethyl sulfoxide (DMSO), nitrogen was introduced and heated at 135-145°C for 1.5-2.5 h. The mixed solution containing PVA was then cooled to 55-65°C and poured into a glass container precooled to 5-10°C. The mixture was placed at -15-25°C for 8-12 h to promote gelation. The formed frozen gel was soaked in distilled water for 90-102 h to completely remove the residual DMSO to obtain PVA hydrogel. (2) Preparation of modified PVA hydrogel: distilled water, the PVA hydrogel prepared in step (1), and glycidyl methacrylate (GMA) are added to a 250 ml three-necked round-bottom flask in sequence, the pH of the mixture is adjusted with nitric acid (HNO3), and the mixture is placed in a shaker at 250-350 rpm for 4-8 hours to obtain a uniformly dispersed suspension, and an acidic cerium ammonium nitrate (CAN) solution is dripped into the suspension as an initiator through a constant pressure reduction funnel at 35-45°C. After reacting for 4.5-5.5 hours, the product is immersed in distilled water for 22-26 hours to remove the homopolymer formed on the surface of the hydrogel, and then the hydrogel is vacuum dried at 35-45°C until the weight reaches a constant value; the dried hydrogel is immersed in a diethylamine aqueous solution at 24-28°C for reaction for 22-24 hours, and finally the product after the reaction is completed is vacuum dried at 35-45°C until the weight reaches a constant level to obtain a modified PVA hydrogel; (3) Preparation of polylactic acid microspheres: polylactic acid was dissolved in dichloromethane containing quinine sulfate to obtain a mixed solution, and the mixed solution was added dropwise to liquid paraffin containing 5 wt% Span 80, and stirred at 350-450 rpm for 20-30 min at 30, 35, and 40 °C, respectively. The dichloromethane was kept at 40 °C for 35-45 h to evaporate, and the obtained microspheres were collected by centrifugation and washed with n-hexane and 2-propanol to obtain polylactic acid microspheres, which were used as sulfate ion donors for SRB. (4) Preparation of hydrogel capable of stably releasing H2S: Sulfate-reducing bacteria (SRB) were cultured in fresh modified Postgate medium to obtain a fresh bacterial suspension, which was further diluted to 5×10 4 CFU / ml, the modified PVA hydrogel prepared in step (2) is cryogenically crushed with liquid nitrogen to obtain its flowable form, and is sterilized under high pressure to eliminate microbial contamination, the sterilized modified PVA hydrogel is added to the SRB suspension, stirred to fully mix the bacteria and the hydrogel material, and a uniform SRB / modified PVA hydrogel mixture is prepared, and finally the SRB / modified PVA hydrogel mixture is evenly mixed with the polylactic acid microspheres prepared in step (3) to obtain a hydrogel that can stably release H2S.
2. The hydrogel capable of stably releasing hydrogen sulfide and the preparation method thereof according to claim 1, characterized in that: In step (1), the mass ratio of polyvinyl alcohol to dimethyl sulfoxide is 1:(5-5.6), and the mass ratio of distilled water to dimethyl sulfoxide is 1:(3.7-4.2).
3. The hydrogel capable of stably releasing hydrogen sulfide and the preparation method thereof according to claim 1, characterized in that: In step (2), the ratio of GMA mass (g), distilled water volume (ml) and PVA hydrogel mass (g) is 1: (98-102): (4.5-4.7); the ratio of GMA mass (g) and CAN (ml) volume is 1: (34-38), and the pH of the mixture is adjusted to 5-6 with nitric acid.
4. The hydrogel capable of stably releasing hydrogen sulfide and the preparation method thereof according to claim 1, characterized in that: The volume ratio of diethylamine to distilled water in step (2) is 1:(0.8-1.2).
5. The hydrogel capable of stably releasing hydrogen sulfide and the preparation method thereof according to claim 1, characterized in that: In step (3), the ratio of the mass (g) of quinine sulfate, the volume (ml) of dichloromethane and the mass (mg) of polylactic acid is 1:(4.5-5.5):(335-425).
6. The hydrogel capable of stably releasing hydrogen sulfide and the preparation method thereof according to claim 1, characterized in that: In step (4), the ratio of the volume (ml) of the SRB suspension to the mass (mg) of the modified PVA hydrogel is 1:(9-11), and the ratio of the volume (ml) of the SRB / modified PVA hydrogel mixture to the mass (g) of the polylactic acid microspheres is 1:(2.5-4.5).